Designing interactive academia-industry framework in digital language classroom / Wan Najmiyyah Wan Md Adnan ... [et al.] - Wan Md Adnan, Wan Najmiyyah; Mohd Radin, Najlaa’ Nasuha; Mohd Adam, Aileen Farida; Hashim, Nooryuhanis (Universiti Teknologi MARA, 2022)
Language pedagogy has recently shifted its focus to digital pedagogy, hence classroom tasks being modified has become an essential practice around the world. One challenging element of teaching in a digital classroom is keeping students interested and ensuring that they have genuine learning experiences. It was also discovered that digital language classrooms give students minimal exposure to real-world settings, especially in English for Professional Interaction digital classrooms as it lacks the tools that connect academics and industry players. This study’s main objective is to conceptualise a framework that uses an educational research and development model that includes industry players as part of the classroom tasks and lesson plans for students’ engagement in the digital language classroom. The study's research design is a 10-stage research and development methodology that includes both quantitative and qualitative data analysis. The study was conducted over the course of four semesters from June 2020 until January 2022 in English for Professional Interaction classrooms. Professional speakers from various industries were invited for online class discussions and feedback was collected after each session. This interactive academia-industry framework in the digital language classroom serves as a methodological design that has the potential to affect students through authentic usage of content for realistic learning experiences.